PENGENALAN ALAT-ALAT BODY REPAIR DAN PELATIHAN DASAR TEKNIK REPAIR BODY MOBIL UNTUK SISWA TEKNIK OTOMOTIF - Muhammad Irfan; Yudi Akbariaji; Boby Saputra; Azriel Alfito Zikry; Muhammad Alfinanda Rizky; Larisang; Agus Suryadi; Indah Kusuma Dewi (Fakultas Ilmu Komputer, 2025)
This community service activity aims to introduce body repair tools and provide basic training on car body repair techniques to Automotive Engineering students at SMK Al Jabar Batam. The program is designed to meet the needs of the automotive industry, which increasingly requires practical skills in car body repair. The training covers the basic theory of various body repair tools used in the industry, as well as the basic techniques applied in car body repair, which includes the process of painting, shaping, and finishing the car body. The methodology used in this training includes theoretical sessions that review the tools used in body repair and safe working procedures. Furthermore, hands-on practical sessions were given to allow students to practice the skills they have learned. This activity was conducted in stages, starting with the introduction of tools and ending with car body repair techniques that comply with automotive industry standards. The use of personal protective equipment (PPE) is also taught to ensure students' safety during the training process. The expected outcome of this training is the improvement of students' practical skills in using body repair tools and their ability to repair car bodies. With these skills, students are expected to be ready to enter the workforce and have higher competitiveness in the automotive industry. This program also aims to improve the students' readiness for the automotive industry.